Ac-SDKP Attenuates Activation of Lung Macrophages and Bone Osteoclasts in Rats Exposed to Silica by Inhibition of TLR4 and RANKL Signaling Pathways - Jin F; Geng F; Xu D; Li Y; Li T; Yang X; Liu S; Zhang H; Wei Z; Li S; Gao X; Cai W; et al. (Dove Medical Press, 2021)
Fuyu Jin,1 Fei Geng,2 Dingjie Xu,3 Yaqian Li,1 Tian Li,1 Xinyu Yang,1 Shupeng Liu,1 Hui Zhang,1 Zhongqiu Wei,1 Shifeng Li,2 Xuemin Gao,2 Wenchen Cai,2 Na Mao,2 Xue Yi,4 Heliang Liu,2 Ying Sun,1 Fang Yang,2 Hong Xu1,2 1Basic Medical College, Hebei Key Laboratory for Chronic Diseases, North China University of Science and Technology, Tangshan, Hebei Province, 063210, People’s Republic of China; 2School of Public Health, Hebei Key Laboratory for Organ Fibrosis Research, North China University of Science and Technology, Tangshan, Hebei Province, 063210, People’s Republic of China; 3Traditional Chinese Medicine College, North China University of Science and Technology, Tangshan, Hebei Province, 063210, People’s Republic of China; 4Key Laboratory of Functional and Clinical Translational Medicine, Xiamen Medical College, Xianmen, Fujian Province, 361023, People’s Republic of ChinaCorrespondence: Hong Xu 21 Bohai Road, Caofeidian District, Tangshan, Hebei Province, 063210, People’s Republic of ChinaTel +86 315-8816236Email xuhong@ncst.edu.cnBackground: Silica-induced inflammatory activation is associated with silicosis and various non-respiratory conditions. The present study was designed to examine the anti-inflammatory effects of N-acetyl-seryl-aspartyl-lysyl-proline (Ac-SDKP) on lung macrophages and bone osteoclasts after silica inhalation in rats.Methods: Wistar rats and NR8383 and RAW 264.7 cell lines were used in the present study. The receptor activator of nuclear factor kappa-B ligand (RANKL) and toll-like receptor 4 (TLR4) signaling pathways was measured in the lung tissue of rats or NR8383/RAW 264.7 cells exposed to silica. The microarchitecture of the trabecular bone in the tibia and femur was evaluated in silicotic rats. Furthermore, the roles of Ac-SDKP on silicotic rats, silica-treated NR8383/RAW 264.7 cells, and RANKL-induced osteoclast differentiation were studied.Results: The data indicated that silica inhalation might activate the RANKL and TLR4 signaling pathways in lung macrophages, thus inducing the lung inflammatory and proteolytic phenotype of macrophages and osteoclasts in lung and bone. Ac-SDKP maintained the lung elastin level by inhibiting lung inflammation and macrophage activation via the RANKL and TLR4 signaling pathways. Ac-SDKP also attenuated the reduction in femoral bone mineral density in silicotic rats by inhibiting osteoclast differentiation via the RANKL signaling pathway.Conclusion: Our findings support the hypothesis that inhalation of crystalline silica induces activation of lung macrophages and bone osteoclasts via the RANKL and TLR4 signaling pathways. Ac-SDKP has the potential to stabilize lung homeostasis and bone metabolism.Keywords: silicosis, N-acetyl-seryl-aspartyl-lysyl-proline, macrophage, osteoclast